2020
DOI: 10.1007/s00432-020-03179-w
|View full text |Cite
|
Sign up to set email alerts
|

The function of Piezo1 in colon cancer metastasis and its potential regulatory mechanism

Abstract: Objective Increasing evidence has revealed that mechanical stress and elevated mechanical signals promote malignant tumor transformation and metastasis. This study aimed to explore the function of the mechanically activated ion-channel Piezo1 in the colon cancer metastasis and its potential regulatory mechanism. Methods First, we examined the expression levels of Piezo1 and mitochondrial calcium uniporter (MCU) both in colon cancer tissues and assessed the prognostic value of Piezo1 and MCU in a colon cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 38 publications
4
85
0
Order By: Relevance
“…Intriguingly, our results indicated that MCU expression was significantly higher in omental metastasis than gastric cancer tissues, indicating that MCU expression might contribute to gastric cancer metastasis. Combining previous studies, MCU has been confirmed to promote several cancer metastasis, such as colon cancer 10 and hepatocellular carcinoma. 11 We found that MCU knockdown In gastric cancer tissues, there was an increase in expression of HIF-1α and Vimentin and loss of E-cadherin.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Intriguingly, our results indicated that MCU expression was significantly higher in omental metastasis than gastric cancer tissues, indicating that MCU expression might contribute to gastric cancer metastasis. Combining previous studies, MCU has been confirmed to promote several cancer metastasis, such as colon cancer 10 and hepatocellular carcinoma. 11 We found that MCU knockdown In gastric cancer tissues, there was an increase in expression of HIF-1α and Vimentin and loss of E-cadherin.…”
Section: Discussionmentioning
confidence: 54%
“…As previous studies, MCU expression is associated with HIF-1α signaling pathway in TNBC 8 and colon cancer. 10 Thus, in this study, we detected the expression of MCU, submit your manuscript | www.dovepress.com…”
Section: Abnormal Expression Of Mcu Hif-1α Vegf and E-cadherin Protmentioning
confidence: 87%
See 1 more Smart Citation
“…As tumor cells grow, the mechanical forces within the tumor and TME increase, and the mechanosensitive cation channels are activated by these mechanical signals and interact with focal adhesions to regulate tumor development [ 171 ]. Recent research showed that the Piezo1 channel is closely correlated with some types of cancers, including oral squamous cell carcinoma, prostate cancer and colon cancer [ 172 174 ]. Furthermore, the Piezo2 channel has been shown to play a role in the proliferative changes and angiogenesis of brain metastatic cells and bladder cancer [ 175 ].…”
Section: Function Of Piezo Channelsmentioning
confidence: 99%
“…The Piezo1 channel enhances the invasive phenotype in multiple tumors, namely breast, colorectal and prostate cancers [ 193 , 287 , 288 ]. An electrophysiological study described that heterologously expressed Piezo1 channels are inhibited by extracellular protons [ 188 ].…”
Section: Ph-dependent Regulation Of Ion Channels In Cancer Cellsmentioning
confidence: 99%